Persistence of Neuropsychological Deficits Following Pediatric Critical Illness. Issue 8 (August 2015) - Als, Lorraine C.; Tennant, Anna; Nadel, Simon; Cooper, Mehrengise; Pierce, Christine M.; Garralda, M. Elena
Abstract : Objective: To study 12-month persistence of neuropsychological deficits in PICU survivors. Design: Prospective follow-up study. Setting: Two PICUs. Participants: Children 5–16 years old with neuropsychological deficits 3–6 months following PICU care for meningoencephalitis, sepsis, and other critical illnesses (excluding other primary neurological disorders). Interventions: None. Measurements and Main Results: Neuropsychological function was assessed using the Cambridge Neuropsychological Test Automated Battery, the Children's Memory Scale, and the Wechsler Abbreviated Scale of Intelligence or Wide Range Intelligence Test. Forty-seven of 88 PICU admitted children (53%) were identified as neuropsychologically impaired 3–6 months after discharge; of these, 23 provided 12-month follow-up data. In spite of significant improvements in measures of memory, there was little change in intelligence quotient and visual attention over the study period, and children's educational progress remained below expectation. Conclusions: We found persistently reduced neuropsychological function following PICU admission in the critical illnesses under study. Abstract : Supplemental Digital Content is available in the text.